Accuracy of Partial and Complete-Arch Conventional Versus Digital Impressions: An In-Vitro Study - Jeremy Chieng; Daniel Lee; Nicole Lim; Sydney Yu; Sunee Limmeechokchai; Joseph Kan; Udochukwu Oyoyo; John Won (Journal of the California Dental Association)
Background Digital impressions offering an alternative method that promises to enhance precision, reduce patient discomfort and streamline workflows. However, it is essential to compare the accuracy of both partial and complete arch impressions using conventional and digital techniques to provide evidence-based data that can guide dental professionals in selecting the most accurate and reliable method for different clinical scenarios. Ultimately, the goal is that these factors will lead to improved patient outcomes and advancing dental practices.Objectives To evaluate the accuracy of partial and complete arch impressions using conventional and digital techniques through an in-vitro 3D analysis.Materials and Methods Typodonts with zirconia crown preparation on tooth #19 along with grooves were prepared for alignment. Partial (PAS) and full (FAS) arch digital impressions were obtained using the intraoral scanner. Partial (PAC) and full (FAC) arch conventional impressions were made with vinyl polysiloxane (VPS) impression material, processed into a gypsum study cast and scanned with an intraoral scanner. A total of 120 STL files were superimposed and analyzed using three-dimensional analysis software.Results All experimental groups (PAS, FAC, and PAC) were statistically different from the control group (FAS). PAS demonstrated the least deviation (10.33 ± 29.00 μm) while PAC demonstrated the highest deviation (125.2 ± 81.88 μm) (Repeated ANOVA test, p < 0.05) with a deviation in the y-axis (occluso-gingival) contributing the majority of the deviations.Conclusion Within the limitations of this study, the accuracy of the partial arch digital impressions was comparable to complete arch digital impressions. Therefore, we would reject the null hypotheses of our study. The results indicated that the highest deviation appeared on the occluso-gingival axis.